A label-free quantitative proteomic investigation reveals stage-responsive ripening genes in apricot fruits. Issue 3 (4th May 2017) - Zhang, Wentao; Li, Xihong; Li, Li; Tang, Yao; Qi, Wei; Liu, Xia; Qiao, Liping; Wang, Wei; Jia, Xiaoyu
ABSTRACT: Apricot ( Prunus armeniaca L.), a member of the Rosaceae family, with favorable nutritional and flavour quality, exhibited the characteristic climacteric changes during the fruit ripening process in 'Shushanggan' apricot. To further confirm the ripening-related genes in apricot, we combined quantitative proteomic tools with bioinformatics to investigate the expression profiles of ripening genes involved in significant biochemical and metabolic changes during ripening stages. The results showed that physiological traits of apricot fruits varied significantly at three different ripening stages, with remarkable correlation with fruit quality changes. Furthermore, 128 stage-specific proteins that are differently expressed in a stage-responsive manner in ripening apricot fruits were identified. Hierarchical clustering of stage-responsive proteins also revealed the metabolic changes in accordance with fruit ripening. Hence, a link has been established between protein profiles and ripening phenotypes which will help to improve our understanding of apricot fruit ripening at the proteomic level.